2022
DOI: 10.1029/2022gl099115
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Rate of a Salt Marsh From the 1700 CE Cascadia Subduction Zone Earthquake, Netarts Bay, Oregon

Abstract: Since the 1700 CE Cascadia Subduction Zone earthquake and associated coseismic subsidence and tsunami, vegetated intertidal habitats have reestablished across Pacific Northwest estuaries, yet timescales and mechanisms of recovery are uncertain. We investigated the timescale of salt marsh reestablishment in Netarts Bay, Oregon following the 1700 CE earthquake using a combination of excess 210Pb, 14C, stratigraphic constraints, and Bayesian age‐depth modeling. Coseismic subsidence lowered the area to low/mid mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…For example, Benson et al (2001) found a recovery time of roughly 100 years for Sitka spruce (Picea sitchensis) to recolonize sites following the 1700 earthquake. Recent work by Peck et al (2022) found a 200-year recovery post-CSZ rupture for high marsh at nearby Netarts Bay, Oregon. These recovery rates, however, depend significantly on the balance between relative interseismic SLR and overall sediment supply, which in the LCRE has greatly decreased over the past century (Gelfenbaum et al, 2001;Templeton & Jay, 2013).…”
Section: Habitat Successionmentioning
confidence: 99%
“…For example, Benson et al (2001) found a recovery time of roughly 100 years for Sitka spruce (Picea sitchensis) to recolonize sites following the 1700 earthquake. Recent work by Peck et al (2022) found a 200-year recovery post-CSZ rupture for high marsh at nearby Netarts Bay, Oregon. These recovery rates, however, depend significantly on the balance between relative interseismic SLR and overall sediment supply, which in the LCRE has greatly decreased over the past century (Gelfenbaum et al, 2001;Templeton & Jay, 2013).…”
Section: Habitat Successionmentioning
confidence: 99%